Intercellular Interactions in Immunocompetent Sphere at Rheumatoid Arthritis Following the Application of Hematopoietic Embryonic Liver Cells - Goltsev, A. N.; Rassokha, I. V.; Lutsenko, E. D.; Dubrava, T. G.; Ostankova, L. V. (Problems of Cryobiology and Cryomedicine, 2003)
Using the rheumatoid arthritis’ experimental model in mice there was studied the therapeutic effect of native and cryopreserved hematopoietic embryonic liver cells (HELCs). Having used the certain spectrum of indices, there was demonstrated the HELCs capability to correct the key mechanisms of adjuvant arthritis development, determined by the character and degree of cooperative interactions of immune system (IS) substrates. There have been shown the differences in the correcting effect of cryopreserved HELCs comparing to the native ones that may be stipulated by the change in their structural and functional organization following the effect of cryopreservation factors.